If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + 9 = 7x + 31 Reorder the terms: 9 + 14x = 7x + 31 Reorder the terms: 9 + 14x = 31 + 7x Solving 9 + 14x = 31 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 9 + 14x + -7x = 31 + 7x + -7x Combine like terms: 14x + -7x = 7x 9 + 7x = 31 + 7x + -7x Combine like terms: 7x + -7x = 0 9 + 7x = 31 + 0 9 + 7x = 31 Add '-9' to each side of the equation. 9 + -9 + 7x = 31 + -9 Combine like terms: 9 + -9 = 0 0 + 7x = 31 + -9 7x = 31 + -9 Combine like terms: 31 + -9 = 22 7x = 22 Divide each side by '7'. x = 3.142857143 Simplifying x = 3.142857143
| -3(x-7)+9x=6x+11 | | 4(6-y)+10=-10(y-2)-9 | | 3v+v-3v=9 | | 5=7-9 | | 8.425-3.143x=9.214x+12.081 | | a+7=-14 | | -42x-12=-6(6x-4) | | -13=12+m | | c=3+-3 | | -1+n=-20 | | -11x+10=-12x+8 | | 9x+3y+1y-0.9x= | | 10y-17=6y-12 | | -6x-10=38 | | 9x^2+18x-39=0 | | -10=h-6 | | -9+13x=11-x | | 5.39x+16=29.0521+4x | | 11-5x+3=2x+4-3x | | -13m+14-11=7(-m+13)+2 | | 15x+2=9x+22 | | 7(7y+17)=16+8(5y+5) | | 4x^5-22x^3-80x=0 | | -6p+7=-5(2p+13) | | 10(2)-3x=15 | | -16w=8(-w+6) | | r^2-2r^2+3r^2= | | (2dc)(4c^2d^5)= | | -20j+3j+19=-9(3j+18)-19 | | 10(0)-3x=15 | | 7(-r-15)+9r=9r | | (3x-3)*2x=84 |